2006
DOI: 10.1074/jbc.m512121200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bicyclic Peptide Neuropilin-1 (NP-1) Antagonist (EG3287) Reveals Importance of Vascular Endothelial Growth Factor Exon 8 for NP-1 Binding and Role of NP-1 in KDR Signaling

Abstract: Neuropilin-1 (NP-1) is a receptor for vascular endothelial growth factor-A 165 (VEGF-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 59 publications
6
138
2
2
Order By: Relevance
“…2). It was further shown that a peptide corresponding to the exon 8 encoded region effectively blocked VEGF165 binding to Nrp expressing cells (36). Our data strongly support that it is the C-terminal tail encoded by exon 8 that is the site of direct interaction between VEGF165 and Nrp and provides a structural basis for this interaction (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…2). It was further shown that a peptide corresponding to the exon 8 encoded region effectively blocked VEGF165 binding to Nrp expressing cells (36). Our data strongly support that it is the C-terminal tail encoded by exon 8 that is the site of direct interaction between VEGF165 and Nrp and provides a structural basis for this interaction (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…The C terminus of Tuftsin interacts with the third ligand binding loop, with specific interactions with residues S346, T349, and Y353. The importance of a C-terminal arginine for interactions with Nrp at this site explains the observation that chemical alteration of the C terminus of inhibitory peptides to a carboxyamide results in complete loss of inhibition (36). Additionally, placental growth factor-2, which binds N1b1b2, also possesses a C-terminal arginine (24,37).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, the R14A/R49A mutant was only minimally affected in the NRP1 binding assay, suggesting that the key residues required for NRP1 binding to VEGF164 are distinct from those at the core of heparin interactions. Based on the present results, we speculate that the NRP1 binding site is composed of multiple amino acids, including those associated with heparin binding, that function cooperatively in forming an extended binding surface and that may also include residues derived from exon 8 (55,56). A surprising discovery reported by Shintani et al (57) was that binding of VEGF to NRP1 is increased due to the presence of heparan sulfate or chondroitin sulfate chains covalently linked to the NRP1 core protein in endothelial and smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide significantly inhibited VEGF-A165a binding to NRP1 while lacking most of the exon 7-encoded domain and comprising largely of the exon 8a-encoded sequence (Fig. 3 of 25 ). The peptide inhibited VEGF-A165a-induced VEGFR2, PLC-γ and ERK activation in HUVECs.…”
Section: Evidence That the Exon 8a Domain Which Vegf-a121a Has Is Rmentioning
confidence: 99%